Calvin and Hobbes Sunday pages : 1985-1995 - Watterson, Bill (Andrews McMeel Publishing, in cooperation with the Ohio State University Cartoon Research Library, 2001)
Along with his comments about the thirty-six Sunday pages he chose for the exhibit, Watterson reflects on the cartoon from the perspective of six years, and provides insight into his life as a syndicated cartoonist.